Case report: Recovery and sequential imaging of a patient with osmotic demyelination syndrome - Harris, Stephanie; Dupanloup, Adrien; Liao, Pen-Ting; Jukier, Tom (Frontiers in Veterinary Science, 2023)
A 4-year-old neutered-male Australian Shepherd was presented to an emergency and referral hospital for an acute onset of neurologic signs and abnormal mentation. Seven days prior, the patient had been diagnosed with hypoadrenocorticism and was treated accordingly at another hospital. Based on recent clinical history, the neurologic signs were consistent with thalamic and brainstem deficits and suspected to be caused by osmotic demyelination syndrome secondary to rapid correction of hyponatremia. A brain MRI confirmed lesions consistent with osmotic demyelination syndrome. The patient’s clinical signs initially worsened, and he required intensive nursing care with multimodal sedation, close monitoring of electrolytes and tailored fluid therapy. The patient recovered and was discharged on day seven of hospitalization. Four and a half months later, re-evaluation of the patient showed complete resolution of the neurological deficits with a now unremarkable neurological exam, and follow-up MRI revealed still present, yet improved bilateral thalamic lesions. This is the first known veterinary case report of sequential brain imaging of a dog that has recovered from osmotic demyelination syndrome. In humans, patients can have evidence of near to full clinical recovery, yet imaging findings may still be abnormal several months after recovery. This report details similar imaging findings in a canine with improved clinical signs, despite persistent lesions on brain MRI. Prognosis of canines with osmotic demyelination syndrome may be better than previously perceived, despite the severity of clinical signs and brain lesions apparent on MRI.